FasL Expression on Human Nucleus Pulposus Cells Contributes to the Immune Privilege of Intervertebral Disc by Interacting with Immunocytes - Liu, Zhi-Heng (Ivyspring International Publisher, 2013)
The mechanisms of immune privilege in human nucleus pulposus (NP) remain unclear. Accumulating evidence indicates that Fas ligand (FasL) might play an important role in the immune privilege of the disc. We aimed for addressing the role of FasL expression in human intervertebral disc degeneration (IDD) and immune privilege in terms of the interaction between NP cells and immunocytes via the FasL-Fas machinery. We collected NP specimens from 20 patients with IDD as degenerative group and 8 normal cadaveric donors as control. FasL expression was detected by qRT-PCR, western blotting and flow cytometry (FCM). We also collected macrophages and CD8+ T cells from the peripheral blood of patients with IDD for co-cultures with NP cells. And macrophages and CD8+ T cells were harvested for apoptosis analysis by FCM after 2 days of co-cultures. We found that FasL expression in mRNA, protein and cellular resolutions demonstrated a significant decrease in degenerative group compared with normal control (p<0.05). FCM analysis found that human NP cells with increased FasL expression resulted in significantly increased apoptosis ratio of macrophages and CD8+ T cells. Our study demonstrated that FasL expression tends to decrease in degenerated discs and FasL plays an important role in human disc immune privilege, which might provide a novel target for the treatment strategies for IDD.